2019
DOI: 10.1111/jfbc.12999
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic acid‐rich Solanum melongena extract has protective potential against rotenone‐induced neurotoxicity in PC‐12 cells

Abstract: Neurodegenerative diseases are major threats to human health. Here, through fluorescence, colorimetric, immunoblotting, spectroscopy, and laser scanning confocal microscopic techniques, we investigated the neuroprotective properties of chlorogenic acid‐rich Solanum melongena extracts (SM extract) in rotenone‐induced PC‐12 cell death. The results showed that rotenone caused apoptosis to PC‐12 cells by elevating Bax/Bcl‐2 ratio and increasing caspase‐3 activity. Rotenone also increased ROS in cells while suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
(42 reference statements)
0
9
0
1
Order By: Relevance
“…The eggplant, exclusively native to the Old World, is an important vegetable worldwide especially in Africa and Southeast Asia (Zhuang et al, 2012), and have been listed by the Food and Agriculture Organization as the fourth largest vegetable crop, owing to their great nutritional and medicinal properties and is rich in proteins, minerals, and antioxidants, such as chlorogenic acid (CGA; 5‐ O ‐caffeoylquinic acid; Alarcon‐Flores et al, 2015). This dietary phenolic acid exhibits anti‐inflammatory, antimutagenic, and antiproliferative activities; however, the mechanism underlying CGA formation in the eggplant remains to be fully elucidated (Meinhart et al, 2019; Youn et al, 2019). In recent years, eggplant production is severely threatened by several soil‐borne diseases and is prone to insect damage (Magioli & Mansur, 2005; Vorontsova et al, 2013); therefore, numerous studies have aimed to elucidate the mechanisms of resistance in eggplant (Uribe et al, 2014; Yang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The eggplant, exclusively native to the Old World, is an important vegetable worldwide especially in Africa and Southeast Asia (Zhuang et al, 2012), and have been listed by the Food and Agriculture Organization as the fourth largest vegetable crop, owing to their great nutritional and medicinal properties and is rich in proteins, minerals, and antioxidants, such as chlorogenic acid (CGA; 5‐ O ‐caffeoylquinic acid; Alarcon‐Flores et al, 2015). This dietary phenolic acid exhibits anti‐inflammatory, antimutagenic, and antiproliferative activities; however, the mechanism underlying CGA formation in the eggplant remains to be fully elucidated (Meinhart et al, 2019; Youn et al, 2019). In recent years, eggplant production is severely threatened by several soil‐borne diseases and is prone to insect damage (Magioli & Mansur, 2005; Vorontsova et al, 2013); therefore, numerous studies have aimed to elucidate the mechanisms of resistance in eggplant (Uribe et al, 2014; Yang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…CGA can cross the blood–brain barrier to protect the brain and reduce the incidence of various brain diseases, such as dementia, Alzheimer disease (AD), Parkinson disease (PD), depression, and ischemia [ 15 , 16 , 17 , 18 , 19 ]. Moreover, cellular studies have demonstrated the cytoprotective and neuroprotective effects of CGA [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, catechins, which represents 36.8% of the material, are polyphenols that have been shown to have protective health benefits through reductions in ROS (Ruidavets et al, 2000;Xiangxin et al, 2002;Hofmann & Sonenshein, 2003;Ohga et al, 2009;Hazafa et al, 2019;Wang et al, 2019). Additionally, S7 has a high percentage of chlorogenic acids (26.2%), that have been shown to decrease ROS and increase ATP production in cells (Youn et al, 2019). These results converge with previous accounts from our lab and others demonstrating that catechins ((-)-epigallocatechin, -EGC‖, (-)-epigallocatechin-3-gallate, -EGCG‖) and chlorogenic acids may modify ROS generation (Manach et al, 2005;Nemzer et al, 2018).…”
Section: Discussionmentioning
confidence: 99%